Process and outcome of care for patients with ovarian cancer. Issue 6501 (12th October 1985) - Liberati, A; Mangioni, C; Bratina, L; Carinelli, G; Marsoni, S; Parazzini, F; Regallo, M; Talamini, R; Tognoni, G
Abstract : The process and outcome of care for a group of patients with ovarian cancer treated over two years in two groups of Italian general hospitals were investigated. The quality of diagnostic and therapeutic measures did not substantially differ in specialised and non-specialised centres when selected indicators of quality of care were examined. Similarly, no differences in survival emerged for the two groups of hospitals. Overall results of the Italian series compared well with statistics of survival published by international centres for cancer, suggesting that when the yield of available treatments is limited both the process and outcome of care should be evaluated to obtain a reliable picture of quality of care. In the light of these results there are useful implications for planning future clinical trials and ways of caring.